Partner stalking : (Springer Publishing Company, 2006)
This book examines the multiple aspects of partner stalking from the victim's perspective. Female survivors share their personal stories of partner stalking, and the authors provide an extensive look at the latest stalking research providing readers with the new most relevant implications for practice and future research.